Prenuptial Agreement and the Principle of Balanced Justice in the Division of Joint Property in Islamic Marriage Law - Shomad, Abd; Hajati, Sri (Universitas Airlangga, 2025)
The issue of joint property or shared assets (harta gono-gini) is actually a legal area that has not been fully explored, a domain open to ijtihad. The concept of joint property and all its details are not found in the studies of medieval Islamic jurisprudence (fiqh) or classical fiqh. The concepts surrounding joint property have continued to develop and are crucial to be discussed in contemporary studies. The urgent aspect to be researched is the model of managing marital property and the application of the principle of balanced justice in the distribution of marital property within the context of fiqh munakahat and marriage agreements in Islamic law. The research model used is normative juridical with a legislative approach and a conceptual approach. Thus, the result is that joint property, based on qiyas, can be managed through a marriage agreement. If not specified in the marriage agreement, then using the principle of balanced justice found in Islamic inheritance law.